The optimization of zircon analyses by laser-assisted atom probe microscopy: Insights from the 91500 zircon standard - Saxey, David; Reddy, Steven; Fougerouse, Denis; Rickard, William (2017)
© 2018 American Geophysical Union. As a quantitative nanoscale chemical analysis technique, atom probe microscopy (APM) typically requires careful tuning and optimization of data acquisition parameters in order to obtain the highest quality results. While there is growing interest in the analysis of geological materials, including zircon, by APM, a full understanding of the controls on data quality will take time to develop. Optimization depends not only on the material to be analyzed but also on the particular specimen form, and on the information that is sought from the data. The zircon 91500 reference material has been analyzed by APM in order to explore the dependence of key metrics, such as background noise, composition, hit-multiplicity, and complex ion formation, on a number of acquisition conditions. In general, the best results are obtained under “cold” conditions, corresponding to low laser pulse energies. However, the concentration of the major element species tends to improve at higher energies, and there is also an apparent correlation between several metrics and the acquisition voltage, which remains to be fully understood. Several issues that can arise in the analysis of zircon via APM will be raised and discussed in some detail.